Enhancing the Regional Entrepreneurship Ratio in West Lampung Regency through the Competitiveness of Coffee Industry MSMEs - Nurliana, Nurliana (SEAN Institute, 2025)
The entrepreneurship ratio is a crucial indicator in assessing a region's economic capacity and independence. West Lampung Regency currently shows a low entrepreneurship ratio, largely due to the dominance of micro-enterprises and the suboptimal competitiveness of MSMEs in the robusta coffee processing sector—a flagship commodity of the region. This paper aims to formulate policies to enhance the entrepreneurship ratio by improving the competitiveness of coffee-based MSMEs. Using a qualitative descriptive approach through FGDs, literature studies, and policy analysis, the main issue identified was the lack of implementation of processing and marketing standards among most coffee MSMEs. As a result, a policy recommendation has been proposed: the formulation of a Regent Regulation on the Standardization of Robusta Coffee Processing and Marketing, which was deemed the most feasible according to Bardach's four policy criteria (technical, financial, political, and administrative). This policy is expected to improve the quality and market reach of local coffee, encourage business scaling, increase employment, and strengthen the entrepreneurial ecosystem through synergy with gastronomy-based tourism. With the right policies, West Lampung Regency's entrepreneurship ratio has the potential to improve significantly and sustainably.